2009
DOI: 10.1007/s00704-009-0175-0
|View full text |Cite
|
Sign up to set email alerts
|

Available energy and energy balance closure at four coniferous forest sites across Europe

Abstract: The available energy (AE), driving the turbulent fluxes of sensible heat and latent heat at the earth surface, was estimated at four partly complex coniferous forest sites across Europe (Tharandt, Germany; Ritten/Renon, Italy; Wetzstein, Germany; Norunda, Sweden). Existing data of net radiation were used as well as storage change rates calculated from temperature and humidity measurements to finally calculate the AE of all forest sites with uncertainty bounds. Data of the advection experiments MORE II (Tharand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 76 publications
(104 reference statements)
4
43
1
1
Order By: Relevance
“…Barr et al, 2006;Oncley et al, 2007). Our data, however, do not support this idea and indicate rather that the energy budget closure is not suitable to detect the occurrence of advection, as was also found within the ADVEX campaign (Feigenwinter et al, 2008;Moderow et al, 2009). One explanation might be that EC fluxes of water and sensible heat are more robust than CO 2 fluxes as stated by Lee and Hu (2002).…”
Section: Validation Of Ec Flux Correctionscontrasting
confidence: 63%
“…Barr et al, 2006;Oncley et al, 2007). Our data, however, do not support this idea and indicate rather that the energy budget closure is not suitable to detect the occurrence of advection, as was also found within the ADVEX campaign (Feigenwinter et al, 2008;Moderow et al, 2009). One explanation might be that EC fluxes of water and sensible heat are more robust than CO 2 fluxes as stated by Lee and Hu (2002).…”
Section: Validation Of Ec Flux Correctionscontrasting
confidence: 63%
“…Previous studies reported that by considering the storage term, the increment rate of CR was 7 of the average value for 26 site-yr at a site with tall vegetation (Wilson et al, 2002) and 3-12 of the values in four coniferous forest sites (Moderow et al, 2009;Lindroth et al, 2010). Our result is similar to those previous findings.…”
Section: Effect Of the Storage Termsupporting
confidence: 91%
“…where µ is the specific energy conversion due to photosynthesis (0.478 J µmol) and GPP is gross primary production (Moderow et al, 2009). GPP was estimated by measured net ecosystem exchange (NEE).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations